2013
DOI: 10.5301/jn.5000255
|View full text |Cite
|
Sign up to set email alerts
|

Angiopoietin-2 modulates eEOC-mediated renoprotection in AKI in a dose-dependent manner

Abstract: Ang-2 acts as modulator of eEOCs in AKI. The migration analysis indicates that the Ang-2 significantly alters indirect (paracrine) activity of eEOCs, thus promoting renoprotection in a dose-dependent manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 0 publications
1
24
2
Order By: Relevance
“…9,37 In the present study, human umbilical cord blood-derived ECFCs lacked hematopoietic markers (ie, CD45 and CD14) and displayed exclusively markers of endothelial lineage. In NOD-SCID mice, we observed that ECFCs attenuated I/R-induced renal injury, as determined by decreases in plasma creatinine.…”
Section: Protective Effects Of Human Ecfcs In Renal I/r Injurymentioning
confidence: 97%
“…9,37 In the present study, human umbilical cord blood-derived ECFCs lacked hematopoietic markers (ie, CD45 and CD14) and displayed exclusively markers of endothelial lineage. In NOD-SCID mice, we observed that ECFCs attenuated I/R-induced renal injury, as determined by decreases in plasma creatinine.…”
Section: Protective Effects Of Human Ecfcs In Renal I/r Injurymentioning
confidence: 97%
“…Thus, further studies were intended to augment the AKI-protective capacity of PACs and several pharmacological agonists of the cells were identified. Among those were melatonin [47], 8-O-cAMP [51], Bone Morphogenetic Protein-5 (BMP-5) [46], and Angiopoietin-1 [50] and -2 [49]. A more recent study showed that PACs administration post-AKI did not only prevent the kidney from acute loss of excretory function but also stabilizeed certain structural outcome parameters such as interstitial fibrosis and loss of peritubular capillaries [52].…”
Section: Proangiogenic Cells (Pacs) and Endothelial Colony Forming Cementioning
confidence: 99%
“…Both subpopulations, PACs and ECFCs have sucessfully been administered in experimental AKI [44-48]. In addition, several strategies have been established in order to augment AKI-protective effects of particularly PACs [46, 47, 49-51]. In almost all of the mentioned studies, kidney excretory function was evaluated by serum creatinine levels and additionally by certain morphological parameters such as acute tubular damage shortly (48 hours) after ischemia.…”
Section: Proangiogenic Cells (Pacs) and Endothelial Colony Forming Cementioning
confidence: 99%
“…In vivo, ANG2 enhances the proliferative capacity of EPCs [131]. Furthermore, Patschan et al showed that stimulation of EPCs with ANG2 ex vivo prior to transplantation significantly increased their protective effects on renal I/R injury in mice [145]. Dosage likewise plays a crucial role, as either too low or too high concentrations had no positive, or even a pronounced negative effect.…”
Section: Therapeutic Effects Of Ang2mentioning
confidence: 95%